2020
DOI: 10.21203/rs.3.rs-79427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery of Functional Exogenous Proteins by Plant Vesicles to Human Cells in Vitro

Abstract: Background: Plant-derived extracellular vesicles increasingly gain attention as promising carriers of exogenous bioactive molecules to the human cells. Due to their various edible sources they are distinctly biocompatible, biodegradable and easily available in significant amounts. Methods: In present work, extracellular vesicles from grapefruit juice were isolated by differential centrifugation and characterized in terms of size, quantity, and morphology by nanoparticle tracking analysis, dynamic light scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Garaeva et al. successfully used natural grapefruit‐derived extracellular vesicles (GF‐EVs) to effectively deliver exogenous proteins into both human peripheral blood mononuclear cells and colon cancer cells [46] . Another study showed that doxorubicin‐loaded natural GF‐EVs can bypass the blood‐brain barrier and exert significant anti‐glioma efficacy in vivo [50] .…”
Section: The Sources Of Evs and Their Application For Tumor Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Garaeva et al. successfully used natural grapefruit‐derived extracellular vesicles (GF‐EVs) to effectively deliver exogenous proteins into both human peripheral blood mononuclear cells and colon cancer cells [46] . Another study showed that doxorubicin‐loaded natural GF‐EVs can bypass the blood‐brain barrier and exert significant anti‐glioma efficacy in vivo [50] .…”
Section: The Sources Of Evs and Their Application For Tumor Therapymentioning
confidence: 99%
“…Plant‐derived EVs (PDEVs) can also be used for tumor therapy and have attracted more and more interest. PDEVs can be obtained from different parts of plants, such as roots, stems, leaves, fruits, and seeds, and even from dried plant materials [43–49] . They contain abundant microRNAs (miRNAs) that are key regulators of gene expression.…”
Section: The Sources Of Evs and Their Application For Tumor Therapymentioning
confidence: 99%